A STUDY OF SYNTACTIC AND SEMANTIC FEATURES OF ENGLISH EXPRESSIONS OF EXISTENCE IN ENGLISH WITH REFERENCE TO THEIR VIETNAMESE EQUIVALENTS / Nguyen Thi Thu Ha; GVHD: Dang Ngoc Huong - Nguyen, Thi Thu Ha
My graduation thesis “A study of syntactic and semantic features of English expressions of existence in English with reference to their Vietnamese equivalents” involves the analysis of the syntactic and semantic features of English existential expressions with reference to their Vietnamese equivalents. In this study, the qualitative and quantitative research approach, namely the descriptive and contrastive methods were adopted in combination with data collection and data analysis methods in order to find out the syntactic and semantic features of English expressions of existence in English with reference to their Vietnamese equivalents. The findings of the study showed that five types of existential expressions in English have been described syntactically. All of them are structured with three main parts sequenced in the order: S + V + C where the subject is an indefinite noun, except for the verb have/have got and other like verbs. The verbs used in the structures are mostly the verb be and other stative verbs. When the structure is used with there + be, unlike the other four types described, the real subject stands after the verb be. As far as what they mean, English existential sentences can be divided into four semantic groups: Indicating location, referring to actions or occurrences, stating facts or truth, referring to the existence of the initial factor of a series of events.Their Vietnamese equivalents show that existential sentences in both languages have many features in common not only in structure but also in meaning, which facilitates the language learning of Vietnamese learners. Based on the results of the survey, common errors made by Lao Cai Teacher Training College students were detected. From these findings, this study offers some implications which could be beneficial for teaching, learning and translating expressions of existence in English